Negative pressure wound therapy using a portable single‐use device for free skin grafts on the distal extremity in seven dogs. Issue 9 (September 2016) - Miller, AJ; Cashmore, RG; Marchevsky, AM; Havlicek, M; Brown, PM; Fearnside, SM
Abstract : Objective: Retrospective study to describe clinical experience with a portable single‐use negative pressure wound therapy device after application of full‐thickness meshed skin grafts to wounds on the distal extremities of seven dogs. Methods: Seven dogs were treated with portable NPWT after receiving skin grafts; six as the result of tumour resection and one for traumatic injury. Medical records were reviewed and data recorded on patient signalment, cause and location of wound, surgical technique, application and maintenance of portable NPWT, graft survival and outcome, and complications encountered with the system. Clinical outcomes: NPWT was provided for between 4 and 7 days. Five patients were discharged from hospital during the treatment period. Application and maintenance of the portable device was technically easy and no major complications were encountered. Minor complications consisted of fluid accumulation in the evacuation tubing. All dogs achieved 100% graft survival. Conclusions: Application and maintenance of the portable device was technically straightforward. All dogs receiving portable NPWT after transfer of a free skin graft to the distal extremity had a successful outcome.